2019
DOI: 10.1523/jneurosci.1683-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Intrinsic Pain Inhibitory Circuit from the Midcingulate Cg2 to Zona Incerta Alleviates Neuropathic Pain

Abstract: Neuropathic pain is one of the most common and notorious neurological diseases. The changes in cerebral structures after nerve injury and the corresponding contributions to neuropathic pain are not well understood. Here we found that the majority of glutamatergic neurons in the area 2 of midcingulate cortex (MCC Cg2 Glu) were inhibited by painful stimulation in male mice. Optogenetic manipulation revealed that these neurons were tonically involved in the inhibitory modulation of multimodal nociception. We furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
28
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 43 publications
6
28
2
Order By: Relevance
“…The current study also observed that, in resting state, there is decreased activity of the left MCC, a key region connected to circuits mediating cognitive control, nociceptive perception and multisensory integration [32,33]. Particularly, it is suggested that the consecutive hyperactivation of the MCC could alleviate the neuropathic pain, but the hypoactivity of the MCC may diminish the pain inhibitory abilities, corresponding to the present findings [32].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The current study also observed that, in resting state, there is decreased activity of the left MCC, a key region connected to circuits mediating cognitive control, nociceptive perception and multisensory integration [32,33]. Particularly, it is suggested that the consecutive hyperactivation of the MCC could alleviate the neuropathic pain, but the hypoactivity of the MCC may diminish the pain inhibitory abilities, corresponding to the present findings [32].…”
Section: Discussionsupporting
confidence: 85%
“…The current study also observed that, in resting state, there is decreased activity of the left MCC, a key region connected to circuits mediating cognitive control, nociceptive perception and multisensory integration [ 32 , 33 ]. Particularly, it is suggested that the consecutive hyperactivation of the MCC could alleviate the neuropathic pain, but the hypoactivity of the MCC may diminish the pain inhibitory abilities, corresponding to the present findings [ 32 ]. This study provided evidence for functional changes from the left MCC to the left insula, which is localized near to the limbic system, subcortical network and anterior DMN, and may trigger pain processing adjustments in multiple instinct brain networks.…”
Section: Discussionmentioning
confidence: 67%
“…In our previous study, we reported that in vivo silencing of MCC activity using optogenetic tools led to an attenuation of peripheral inflammation-induced mechanical hypersensitivity of the injected hind paw (with Complete’s Freund adjuvant) 19 . More recently, Hu and colleagues discovered that projections arising from subregions of the MCC could selectively modulate neuropathic pain 18 , further supporting our current findings that the MCC could indeed be an important cortical hub that is widely recruited during pathological pain arising from peripheral inflammation and injuries.…”
Section: Discussionsupporting
confidence: 86%
“…There are differences in findings between this study and previous rodent studies. Most notably, this study did not identify any significant effects of zona incerta DBS on mechanical pain thresholds, while hind paw withdrawal thresholds were seen to increase in rodent models of neuropathic pain 7,8,10 . Although unexpected, this may arise from a variety of differences between our study and those performed in rodent models.…”
Section: Discussioncontrasting
confidence: 70%
“…The same group later demonstrated that 50-60 Hz stimulation of zona incerta reduces hyperalgesia in a rat model of neuropathic pain, providing a proof of concept for analgesic zona incerta DBS 7 . More recent work has established compelling causative links between GABAergic output from zona incerta, neuropathic pain, and neuromodulatory relief of hyperalgesia and allodynia 8-10 .…”
Section: Introductionmentioning
confidence: 99%